Imaging and Risk Stratification in Pulmonary Arterial Hypertension: Time to Include Right Ventricular Assessment - Alandejani, Faisal; Hameed, Abdul; Tubman, Euan; Alabed, Samer; Shahin, Yousef; Lewis, Robert A.; Dwivedi, Krit; Mahmood, Aqeeb; Middleton, Jennifer; Watson, Lisa; Alkhanfar, Dheyaa; Johns, Christopher S.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Current European Society of Cardiology and European Respiratory Society guidelines recommend regular risk stratification with an aim of treating patients with pulmonary arterial hypertension to improve or maintain low-risk status (<5% one-year mortality). Methods: Consecutive patients with PAH who underwent cardiac magnetic resonance imaging (cMRI) were identified from the ASPIRE registry. Kaplan Meier survival curves, locally weighted scatterplot smoothing regression and multi-variable logistic regression analysis were performed. Results: In 311 consecutive, treatment-naïve patients with pulmonary arterial hypertension undergoing cMRI including 121 undergoing follow-up cMRI, measures of right ventricular function including right ventricular ejection fraction and right ventricular end systolic volume and right atrial area had prognostic value. However, only right ventricular metrics were able to identify a low-risk status. Age (p<0.01) and right ventricular ejection fraction (p<0.01) but not right atrial area were independent predictors of 1-year mortality. Conclusion: This study highlights the need for guidelines to include measures of right ventricular function rather than right atrial area alone to aid the risk stratification of patients with pulmonary arterial hypertension.